2007
DOI: 10.1021/es071726z
|View full text |Cite|
|
Sign up to set email alerts
|

Voltammetric Detection of Cr(VI) with Disposable Screen-Printed Electrode Modified with Gold Nanoparticles

Abstract: Gold nanoparticle (Au-NP) enhanced voltammetric detection of Cr(VI) is developed for determination of trace amounts of Cr(VI) in an acetate buffer media (pH 4.6). The Au-NPs were electrodeposited onto a disposable screen printed electrode (SPE) via an electrodeposition step. It was found that the electrodeposited Au-NP has strong adsorption on Cr(VI) species, which results in an enhanced reduction current of Cr(VI). Compared with the bulk gold electrode, the reduction current of Cr(VI) was enhanced 10 times wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(35 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…While bulk gold is chemical inert, recent studies show that nanosized GNPs exhibit extraordinary catalytic activity [102][103][104], which is utilized by several studies in electrochemical biosensing [105][106][107][108][109]. The catalytic properties of GNPs, which are believed to originate from the quantum scale dimension [110], the large surface-to-volume ratio and the interface-dominated properties [111,112], can decrease overpotentials of many analytically important electrochemical reactions, realize the reversibility of some redox reactions, and might even allow fabrication of enzyme-free biosensors.…”
Section: Gnps Act As Electrocatalystmentioning
confidence: 99%
“…While bulk gold is chemical inert, recent studies show that nanosized GNPs exhibit extraordinary catalytic activity [102][103][104], which is utilized by several studies in electrochemical biosensing [105][106][107][108][109]. The catalytic properties of GNPs, which are believed to originate from the quantum scale dimension [110], the large surface-to-volume ratio and the interface-dominated properties [111,112], can decrease overpotentials of many analytically important electrochemical reactions, realize the reversibility of some redox reactions, and might even allow fabrication of enzyme-free biosensors.…”
Section: Gnps Act As Electrocatalystmentioning
confidence: 99%
“…Au nanoparticles have attracted considerable attention in electrochemical field because of their advantages of catalysis, mass transport, high effective surface area and control over surrounding environment (Liu and Ju, 2003;Liu et al, 2007;Tangkuaram et al, 2007;Suprun et al, 2008;Jia et al, 2009). It is shown that the catalytic performance of Au nanoparticles is markedly dependent on the structure of their local microenvironment (Miscoria et al, 2005;Welch and Compton, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Some mercury-free solid electrodes, such as bismuth film electrodes [97,147,148] or stannum film electrode [164], have been proposed as a substitute to the mercury liquid electrodes. Recently, the disposable screen-printed electrodes modified with poly-l-histidine film [165], gold nanoparticles [166] and silver or gold nanoparticles [167] have been applied as a voltammetric sensors for the voltammetric determination of Cr(VI). Moreover, nano-sized gold particles deposited on glassy carbon [168] or on the conductive substrate modified with sol-gel derived thiol [169] were also used to the mention above purpose.…”
Section: Recent Trends In the Development Of Voltammetric Sensors Appmentioning
confidence: 99%